2004
DOI: 10.1063/1.1742697
|View full text |Cite
|
Sign up to set email alerts
|

Quantum pathways for resonance energy transfer

Abstract: A quantum electrodynamical calculation is presented that focuses individually on the two quantum pathways or time orderings for resonance energy transfer. Conventional mathematical procedures necessitate summing the quantum pathway amplitudes at an early stage in the calculations. Here it is shown, by the adoption of a different strategy that allows deferral of the amplitude summation, that it is possible to elicit key information regarding the relative significance of the two pathways and their distinct dista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 23 publications
0
36
0
Order By: Relevance
“…[The latter assertion has been explicitly proven for the case of resonance energy transfer (RET) -see ref 27 and the V tensor that appears in that connection is of precisely the same form as arises here.] The apparent paradox is resolved on recall of the time-energy uncertainty principle, and the ultrafast timescale associated with virtual photon propagation over nanoscale distances.…”
Section: Limitations Of the Classical Interpretationmentioning
confidence: 71%
“…[The latter assertion has been explicitly proven for the case of resonance energy transfer (RET) -see ref 27 and the V tensor that appears in that connection is of precisely the same form as arises here.] The apparent paradox is resolved on recall of the time-energy uncertainty principle, and the ultrafast timescale associated with virtual photon propagation over nanoscale distances.…”
Section: Limitations Of the Classical Interpretationmentioning
confidence: 71%
“…Its retarded characteristic applies over all distances, accommodating readily identifiable short-range (near-field, 1 kR  ) and long-range (wave-zone, 1 kR  ) asymptotes. The former behavior is identified with virtual photon coupling (resonance energy transfer) -the latter, real photon propagation (radiative transfer) [11]. Thus, as the detector is moved outwards, away from the near-field, a progressively radiative character to the energy transfer emerges.…”
Section: ( )mentioning
confidence: 99%
“…This, however, is an interpretation whose extension to higher multipoles has a potential pitfall. For example, it is not widely understood that electric quadrupole decay produces radiation that is detectable not only by quadrupole detectors, but also by a dipole detector -yet a clearly non zero result [9,[11][12][13] emerges for the latter case of E2-E1 coupling. This and other processes are both fully allowed and addressed by the general QED theory; in all cases the source-detector coupling is achieved by regular spin-1 photon [14].…”
Section: ( )mentioning
confidence: 99%
“…This radiative term manifests the long-range emergence of the coupling photon into a real character. Revisiting the underlying QED theory in order to disentangle the quantum pathways, recent work 34 has also shown that this long-range behaviour is completely identifiable with the physically more intuitive sense of propagation for the virtual photon-case (a) in Fig. 14.3, or the lower pathway in Fig.…”
Section: Features Of the Pair Transfer Ratementioning
confidence: 99%